The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/ppul.23245
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bedside pulmonary function in the neonate: From the past to the future

Abstract: Pulmonary function testing and monitoring plays an important role in the respiratory management of neonates. A noninvasive and complete bedside evaluation of the respiratory status is especially useful in critically ill neonates to assess disease severity and resolution and the response to pharmacological interventions as well as to guide mechanical respiratory support. Besides traditional tools to assess pulmonary gas exchage such as arterial or transcutaenous blood gas analysis, pulse oximetry, and capnograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 103 publications
(107 reference statements)
1
26
0
1
Order By: Relevance
“…This allows extended recordings in babies who are respiratory unstable or use equipment that may preclude the use of a facemask, primarily continuous positive airway pressure (CPAP) or high-flow nasal cannulas (HFNCs). In accordance with previous studies, we found that applying a facemask significantly increased minute ventilation [2, 4, 7]. This finding is physiologically plausible and most likely explained by increased dead space ventilation induced by the facemask or by tactile stimulation of the facial skin.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This allows extended recordings in babies who are respiratory unstable or use equipment that may preclude the use of a facemask, primarily continuous positive airway pressure (CPAP) or high-flow nasal cannulas (HFNCs). In accordance with previous studies, we found that applying a facemask significantly increased minute ventilation [2, 4, 7]. This finding is physiologically plausible and most likely explained by increased dead space ventilation induced by the facemask or by tactile stimulation of the facial skin.…”
Section: Discussionsupporting
confidence: 92%
“…Tidal breathing measurements and monitoring provide valuable information about lung function in infants, and can be used to evaluate lung development and management of respiratory diseases [1, 2]. However, these measurements are currently largely used as research tools because most techniques are complex and time-consuming, require sedation, or involve the application of a facemask that adds dead space and alters the breathing pattern of the infant [1, 36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of ventilation mode, careful monitoring of respiratory function during mechanical ventilation remains essential. Respiratory function monitoring, together with clinical, radiological, and blood gas monitoring, has been found to reduce mortality and morbidity in ventilated infants, and is essential for adjusting ventilator parameters to achieve optimal gas exchange and to assess patient status and outcomes of therapeutic interventions [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Typically, an easier marker protocol (24 markers on the anterior thoraco-abdominal surface) is used for such analysis. The non-invasive bedside evaluation of the respiratory status with OEP is especially useful in critically ill neonates to assess disease severity and the response to pharmacological interventions [63] as well as to guide mechanical respiratory support (e.g., high-frequency oscillatory ventilation) [64] .…”
Section: Breathing Evaluation Of Healthy Subjectsmentioning
confidence: 99%